Video 1_A machine learning algorithm to predict treatment effectiveness for Kawasaki disease in China: a retrospective model development and validation study.mp4 - Xuemei Li (232384) (2025)
Background Kawasaki disease (KD) is the primary cause of acquired heart disease in children. Intravenous immunoglobulin (IVIG) is the first-line therapy for KD; however, IVIG resistance can occur. Reliable treatment efficacy prediction tools for Chinese patients are lacking, which this study aimed to address. Methods This retrospective cohort study enrolled patients diagnosed with KD admitted to Shengjing Hospital of China Medical University and collected data on 36 demographic, clinical, and laboratory parameters. Least Absolute Shrinkage and Selection Operator (LASSO) regression was used to identify key predictive variables. The dataset was divided into training (70%) and validation (30%) sets. Ten models were trained through 10-fold cross-validation, and the training set data were balanced using the ROSE method for oversampling. The performance of each model was evaluated using the area under the receiver operating characteristic curve (AUC), sensitivity, specificity, and accuracy. Patients with KD admitted to Guangzhou Women and Children’s Medical Centre, Guangzhou Medical University, between January 2023 and December 2024 were enrolled as an external validation cohort. Results The CatBoost machine learning algorithm achieved the best comprehensive results (AUC: 0·960; sensitivity: 0·883; specificity: 0·889, and accuracy: 0·887). The internal validation results with CatBoost were AUC: 0·862; 95% confidence interval [CI]: 0·6453–0·7651; sensitivity: 0·716; specificity: 0·877; and accuracy: 0·861. The external validation results were AUC: 0·834; 95% CI: 0·783–0·884; sensitivity: 0·817; specificity: 0·838, and accuracy: 0·835. Conclusions We present a machine learning model that can predict the risk of IVIG non-responsiveness in patients with KD in China. This model may help doctors develop personalized treatment strategies, thus improving the prognosis of KD.